Rice Supply Patterns in Kalimantan Selatan: Part of solution for regional food security - Arief RM Akbar; Alan Dwi Wibowo; Alia Rahmi; Sigit Prabawa (Universitas Lampung, 2019)
South Kalimantan is a largest rice producer in Kalimantan island. More than five years its rice met by their own production, moreover it has supplied to other area such as Kalimantan Tengah, Kalimantan Timur and Kalimantan Utara. In many studies, rice stocks play a critical role in determining the regional’s food security. In recent issues, rice stocks has a wide impact on an array of economic, political, societal stabilities. Unfortunately, most of the land in Kalimantan Selatan is classified as wetlands, where the land productivity is low. Therefore, this study analyzes rice supply patterns in Kalimantan Selatan in order to provide policies development toward rice self-sufficiency. This research is using system dynamics approach to explore the system which then develop any alternatives of rice policies. Eventually, this study provides evidences for the need to consider rice supply system in the regional’s food security policies.